2001
DOI: 10.1055/s-2001-17834
|View full text |Cite
|
Sign up to set email alerts
|

Die Verlagerung des hinteren Steigbügelschenkels. Eine vergessene Methode der Otosklerosechirurgie?

Abstract: The major advantage of this technique is the avoidance of incus necrosis and foreign body reactions related to the material of the prosthesis. Disadvantages are technical plus the longer duration of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…For this explorative retrospective single-center study, 212 surgical cases were identified and were done using the same techniques and standards (18). All surgeries were performed between November 2012 and April 2019.…”
Section: Methodsmentioning
confidence: 99%
“…For this explorative retrospective single-center study, 212 surgical cases were identified and were done using the same techniques and standards (18). All surgeries were performed between November 2012 and April 2019.…”
Section: Methodsmentioning
confidence: 99%